Pemanfatan Limbah Rumah Tangga Guna Peningkatan Kesejahteraan Keluarga di Kelompok Tani Wanita (KWT) - Suripto (AMMA : Jurnal Pengabdian Masyarakat, 2023)
KWT (Women Farmers Group) in Japuhan Hamlet, Sidomulyo Village, Bambanglipuro District, Bantul Regency, Yogyakarta Special Region Province (hereinafter referred to as KWT Japuhan) have not processed and reused the inorganic and organic waste they produce from household waste. The main business of KWT Japuhan is growing vegetables for the needs of its members. Fertilizing plants in KWT Japuhan is done with chemical fertilizers and chemical drugs, this can lead to an unhealthy environment and increased costs which ultimately reduce income. Community service is aimed at solving the problem of increasing the efficiency of KWT Japuhan with lectures on organic and inorganic waste management. The activity was carried out on October 23 2022 at KWT Japuhan, attended by 40 participants. 26 samples were taken. The results showed that the KWT Japuhan participants were very interested in organic waste management through composting and inorganic waste management through the 3R principle (Reduce, Reuse, Recycle).